Modern China - Rana Mitter (Oxford University Press, 2008)
This lively guide covers a range of social issues from the decline of footbinding and the position of women in society, to the influence of television and film, and the role of the overseas Chinese diaspora. It covers many prominent figures as well, such as the Communist leaders, the last emperors, and prominent writers and artists throughout China's history